THE EFFECT OF ONLINE PROJECT-BASED LEARNING ON STUDENTS' WRITING DESCRIPTIVE TEXT IN COLLABORATIVE LEARNING AT SECOND GRADE OF SMK NU AL BAROKAH BABAT - Ahmad Sholichin; M. Luthfi Abdillah (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
Project-based learning is a type of learning that uses tasks as a basis for learning. It is a very innovative learning method for engaging in project work, in which students work individually on building up their learning and on real goods. The goal of this study was to determine the impact of using online project-based learning on student learning skills and writing descriptive texts. The study was conducted in class XI at SMK NU Al Barokah Babat. To determine whether or not online project based learning was successful, the researchers used a pre-experimental approach to evaluate the data using the t-test statistical formula. The findings of this analysis were the pre-test mean of 53,8333 and the post-test mean of 53,8333.